Endovascular stroke therapy may be safe in patients with elevated international normalized ratio - Mundiyanapurath, Sibu; Tillmann, Anne; Möhlenbruch, Markus Alfred; Bendszus, Martin; Ringleb, Peter A. (Journal of neuroInterventional surgery, 2017)
Introduction Endovascular therapy in acute ischemic stroke is safe and efficient. However, patients receiving oral anticoagulation were excluded in the larger trials. Objective To analyze the safety of endovascular therapy in patients with acute ischemic stroke and elevated international normalized ratio (INR) values. Methods Retrospective database review of a tertiary care university hospital for patients with anterior circulation stroke treated with endovascular therapy. Patients with anticoagulation other than vitamin K antagonists were excluded. The primary safety endpoint was defined as symptomatic intracranial hemorrhage (sICH; ECASS II definition). The efficacy endpoint was the modified Rankin scale (mRS) score after 3 months, dichotomized into favorable outcome (mRS 0-2) and unfavorable outcome (mRS 3-6). Results 435 patients were included. 90% were treated with stent retriever. 27 (6.2%) patients with an INR of 1.2-1.7 and 21 (4.8%) with an INR >1.7. 33 (7.6%) had sICH and 149 patients (34.3%) had a favorable outcome. Patients with an elevated INR did not have an increased risk for sICH or unfavorable outcome in multivariable analysis. The additional use of IV thrombolysis in patients with an INR of 1.2-1.7 did not increase the risk of sICH or unfavorable outcome. These results were replicated in a sensitivity analysis introducing an error of the INR of ±5%. They were also confirmed using other sICH definitions (Safe Implementation of Thrombolysis in Stroke (SITS), National Institute of neurological Disorders and Stroke (NINDS), Heidelberg bleeding classification). Conclusions Endovascular therapy in patients with an elevated INR is safe and efficient. Patients with an INR of 1.2-1.7 may be treated with combined IV thrombolysis and endovascular therapy.
First published November 17, 2016
Gesehen am 28.08.2018